Learn From Your Environment: A Visual Literacy Learning Model - (:unkn) unknown (Australasian Society for Computers in Learning in Tertiary Education, 2020)
Based on the presupposition that visual literacy skills are not usually learned unaided by osmosis, but require targeted learning support, this article explores how everyday encounters with visuals can be leveraged as contingent learning opportunities. The author proposes that a learner’s environment can become a visual learning space if appropriate learning support is provided. This learning support may be delivered via the anytime and anywhere capabilities of mobile learning (m-learning), which facilitates peer learning in informal settings. The study propositioned a rhizomatic m-learning model of visual skills that describes how the visuals one encounters in their physical everyday environment can be leveraged as visual literacy learning opportunities. The model was arrived at by following an approach based on heuristic inquiry and user-centred design, including testing prototypes with representative learners. The model describes one means visual literacy could be achieved by novice learners from contingent learning encounters in informal learning environments, through collaboration and by providing context-aware learning support. Such a model shifts the onus of visual literacy learning away from academic programmes and, in this way, opens an alternative pathway for the learning of visual skills. Implications for practice or policy: This research proposes a means for learners to leverage visuals they encounter in their physical everyday environment as visual literacy learning opportunities; M-learning software developers may find the pedagogical model useful in informing their own software; Educators teaching visual skills may find application of the learning model’s pedagogical assumptions in isolation in their own formal learning settings.
Keywords: m-learning; Rhizomatic learning; Visual literacy; Visual communication; Practicebased research